Communication Strategy Carried Out by Komerce in Empowering the Community of Tunjungmuli Village Purbalingga Regency - Ashidiqi, Syifa Qurrotu Aini; Arifin, Hadi Suprapto; Silvana, Tine (Green Publisher Indonesia, 2025)
This study aims to analyze the communication strategy applied by Komerce in empowering the people of Tunjungmuli Village through digital marketing training. Using a qualitative approach and a descriptive case study research type, this study explores how effective communication can support rural community empowerment. The data were collected through in-depth interviews, direct observations, and document analysis, then analyzed using a thematic approach based on the Creswell framework. The results of the study show that Komerce's communication strategy involves four main elements: strong branding, adaptation to people's needs, delivery of evidence of success, and management of informative, educational, and persuasive content. The use of digital marketing applications, such as Komtim, Komform, and Komplace, has been proven to support the development of people's skills in digital marketing. This empowerment has a significant impact on the economic independence of village communities. This research makes a theoretical contribution to the study of communication strategies for community empowerment in the digital era, as well as practical benefits in the form of strategy recommendations for organizations or local governments that want to implement similar programs. In the future, the research recommends expanding empowerment to other villages as well as integrating the potential of local resources to support the sustainability of the program.